Collaborative Spaces: Nodes Within an Accelerated World - Maurizio Busacca; Cassandra Fontana; Beatrice Maria Bellè (Sociologica)
This study investigates the locational patterns and socioeconomic implications of collaborative spaces (CSs) within the Veneto region of Italy from an accelerationist perspective. Through a comprehensive analysis of the CSs distribution, infrastructural correlations, and socioeconomic contexts, this study explores the evolving role of CSs in contemporary urban landscapes. The findings reveal a nuanced picture of CSs localisation, indicating a dispersal pattern across medium- and small-sized cities, rather than concentrating solely on major urban centres. Proximity to productive and reproductive infrastructures has emerged as a consistent theme, underscoring the economic orientation of CSs within local economic systems. Furthermore, this study delves into the ambivalence of CSs, illustrating their dual role as catalysts of knowledge-based capitalism and sites of socioeconomic tensions. Despite their initial intention to foster professional communities, CSs often become enmeshed in the broader processes of economic exploitation and hegemony. By framing CSs within the context of local innovation systems, this study highlights their potential for intensifying knowledge circulation and collaboration among local actors. This study opens avenues for future research into the evolving role of CSs within innovation systems and their broader socioeconomic implications.